Analysis Consumer Preference in the Use of GoFood Services - Suyanto, AMA; Darmawan, Muhammad Adnan (Advances in Social Sciences Research Journal, 2020)
In this modern era, all activities can be carried out easily because of rapid technological progress. Technology really helps human needs and can’t be separated from human lifestyles. The easy of technology and communication that developed has changed the consumption patterns of the people, especially in ordering online food delivery. Now people tend to buy food through digital applications rather than cooking. The highest frequency of food orders is dominated by the use of delivery as much as 2.6 times a week. This study aims to find out which combinations of attributes that make GoFood choose by consumers, and to find out which attributes are the most dominant. This research is a quantitative study with conjoint analysis techniques. The results showed that the combination of attributes were cheap prices, attractive promotions, safe security, fast time & delivery, and ease of payment using cash. The results of the study also showed that the safety attribute was the most important attribute.